WP3: participation in the multi-level governance of European water and biodiversity - a review of case studies - Ortwin Renn; Augustin Berghöfer; Heidi Wittmer; Felix Rauschmayer (Helmholtz-Zentrum für Umweltforschung (UFZ), 2010)
Participation is said to improve decisions on environmental conflicts. When investigating 16 case studies of participatory processes in European Water and Biodiversity Governance, which necessarily is multi-level, the picture becomes blurred: many different forms of participation can be observed, only few of them are well-defined and well organised; most of them are dominated by ad-hoc decisions on whom to include, how to close debates, and how to deal with uncertainty, complexity, and ambiguity. While nearly all of these processes could be improved by a more conscious and careful setting, the application blueprints will necessarily remain out of scope. Natural, cultural and institutional contingencies make each case special and often unique and the multi-level characteristic of European governance of natural resources adds an additional layer of complexity on how to organise participation. The empirical account of whether deliberation can deliver what it promises in theory is still incomplete.
Keywords: 330; Gewässerschutz; Biodiversität; EU-Umweltpolitik; Bürgerbeteiligung; EU-Staaten